2000
DOI: 10.1111/j.1474-919x.2000.tb04436.x
|View full text |Cite
|
Sign up to set email alerts
|

Audubon's Shearwaters Puffinus Iherminieri on Réunion Island, Indian Ocean: behaviour, census, distribution, biometrics and breeding biology

Abstract: Audubon's Shearwater Pufhnus lherminieri is a little known species of petrel. The recent descriptions of a possibly new species (P. atrodorsalis) and a new subspecies (l? 1. colstoni) have suggested that the population breeding on Reunion Island, I! 1. bailloni, may represent a key taxon for understanding the phylogeography of this group in the Indian Ocean. We provide the first detailed information on distribution, abundance, habitat characteristics and breeding biology of the species on Reunion, and asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 24 publications
2
20
1
Order By: Relevance
“…An example of this is the significantly reduced acoustic activity on moonlit nights, a well‐known phenomenon thought to be a predator avoidance mechanism (Bretagnolle et al . , Oppel et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…An example of this is the significantly reduced acoustic activity on moonlit nights, a well‐known phenomenon thought to be a predator avoidance mechanism (Bretagnolle et al . , Oppel et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in many species, moonlight appears to affect colony attendance behaviour even in the apparent absence of direct predation pressures (Day & Cooper ; Bretagnolle et al. ). This suggests that moonlight avoidance might have an innate component, which may have evolved in response to natural selection on predator avoidance acting in the past, and is maintained despite the lack of current selective pressures.…”
Section: Introductionmentioning
confidence: 99%
“…In shearwaters, moonlight avoidance when attending colonies is more evident among non-breeders (Bretagnolle 1990), probably because they are subject to higher predation risk due to the larger amount of time spent outside the nest burrows (Mougeot & Bretagnolle 2000b). Interestingly, in many species, moonlight appears to affect colony attendance behaviour even in the apparent absence of direct predation pressures (Day & Cooper 1995;Bretagnolle et al 2000). This suggests that moonlight avoidance might have an innate component, which may have evolved in response to natural selection on predator avoidance acting in the past, and is maintained despite the lack of current selective pressures.…”
Section: Introductionmentioning
confidence: 99%
“…(e) Location of seabird colonies (according to: Bretagnolle et al 2000, Burger and Lawrence 2001, Le Corre 2001, Le Corre et al 2002 Th e climatological resolution is shown (the seasonal resolution provides very similar maps).…”
mentioning
confidence: 99%